A novel constitution-based personality-job fit theory: harmonizing organizational psychology and traditional Chinese medicine theories - Yusong Zeng; Zihan Wang; Ruifeng Zhang; Lili Tu; Samuel Ken-En Gan (Discover Psychology, 2025)
Abstract Employee mental health is closely associated with the interaction between individual personality traits and workplace demands. A poor fit between job requirements and an employee’s personality profile can lead to psychological strain and decreased well-being. Existing psychological frameworks, such as Holland’s Personality-Job Fit Theory and the Big Five Inventory (BFI-2), have been widely applied to optimise this alignment. This study proposes a novel integration of Traditional Chinese Medicine (TCM) constitution theory into personality–job matching models. The TCM constitution framework, which encompasses physiological and psychological characteristics and predispositions to disease, offers a holistic perspective on individual differences. We demonstrate conceptual and structural compatibility by mapping the nine TCM constitution types to the Big Five personality dimensions, the International Standard Classification of Occupations (ISCO-08), and Holland’s vocational typology. Incorporating TCM constitutional theory may enhance the granularity and personalisation of job-matching strategies to improve employee engagement, performance, mental health, and job satisfaction in organisational and human resource contexts.